Kritisisme konstruktif dan dialog antar generasi: Cara gen Z mengajukan pertanyaan kritis tentang pancasila dan cara menerjemahkannya - Naufal, Muhamad; Ghazy, Muhammad (Maliki Interdisciplinary Journal, 2024)
Currently, students are the first generation to grow up with the development of modern technology, which we usually refer to as generation Z, or the digital native generation, where it cannot be said that this generation cannot live without technology. Thus, it can be concluded that generation Z is the first generation to grow up with modern technology. The nature of each student must have significant differences with developments at that time. Now, as humans enter the twenty-first century, technological developments have developed rapidly and easy access to information certainly requires adequate natural resources. Therefore, critical thinking is one of the skills that is really needed today. In mathematics, critical thinking is also really needed in the process of solving real problems that require problem solving tools. But each generation definitely has different features, so that in the process of developing critical thinking skills must be equal in each generation and era.